THU0403 A Randomised, Open-Label Study to Evaluate the Relative Bioavailability of a Single Dose of Belimumab Administered Subcutaneously by Prefilled Syringe or Autoinjector. (9th June 2015) - Struemper, H.; Murtaugh, T.; Gilbert, J.; Barton, M.E.; Fire, J.; Groark, J.; Fox, N.L.; Roth, D.; Gordon, D.
Abstract : Background: Intravenous belimumab plus standard systemic lupus erythematosus (SLE) care is approved for the treatment of SLE. Subcutaneous self-administration could enhance belimumab treatment options for patients. Objectives: To examine the relative bioavailability, tolerability and safety of a single subcutaneous dose of belimumab in healthy subjects, self-administered using a single-use autoinjector or prefilled syringe. Methods: BEL117100 (NCT01894360 ) examined usability and reliability of two subcutaneous devices. Subjects were randomised 1:1:1:1 to receive 200 mg belimumab via prefilled syringe (injection site: abdomen or thigh) or autoinjector (injection site: abdomen or thigh). Randomisation was stratified by bodyweight (<70 kg, 70-<80 kg, ≥80 kg). Pharmacokinetic (PK) parameters included maximum observed serum concentration (Cmax) and area under the concentration-time curve (AUC[0–∞]). Rates of adverse events (AEs), injection site pain, user errors and device malfunctions were recorded. Results: Of 81 subjects, 52% were male with a mean age of 32.6 years. Successful injection was achieved by 76/81 (94%) subjects. Five subjects experienced delivery errors (1 autoinjector-thigh; 2 autoinjector-abdomen; 2 prefilled syringe-thigh) and were excluded from the PK analysis. The relative bioavailability estimates (90% confidence intervals) of the autoinjector compared with the prefilled syringe were 93.6% (83.2, 105.4) for AUC(0-∞) and 105.2% (94.0, 117.7) for Cmax . Geometric mean serum belimumab Cmax was slightly higher (26.98 vs 25.32 μg/mL) and AUC(0-∞) was slightly lower (701.0 vs 735.2 day/mg/mL) with the autoinjector compared with the prefilled syringe. There was a weak trend toward higher concentrations for thigh injection compared with abdomen for both devices. Exposure ranges largely overlapped between weight categories; a trend of lower average AUC and Cmax with larger bodyweight was observed. Overall, 41 (51%) subjects reported at least one AE. Five (25%) subjects reported an AE in the prefilled syringe-abdomen group compared with 11 to 13 total subjects across the other groups (52–65%). No serious or severe AEs were reported. Nine (11%) subjects reported at least one drug-related AE. Of these, five (25%) subjects were in the prefilled syringe-thigh group and 4 (19%) subjects in the autoinjector-thigh group. The median VAS scores for injection site pain at dosing were low (4.5–12.0 mm) across all groups and 0 for all groups at 1 and 24 hours post dose. Conclusions: These findings demonstrate comparable bioavailability of belimumab delivered subcutaneously by the autoinjector device and the prefilled syringe and support subcutaneous system. Acknowledgements: Study funded by GSK. Louisa Pettinger, PhD, Fishawack Indicia Ltd, UK, assisted with the abstract submission and was funded by GSK. Disclosure of Interest: H. Struemper Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, T. Murtaugh Employee of: Quintiles, contracted by GSK to carry out the study, J. Gilbert Employee of: GlaxoSmithKline (contractor), M. Barton Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, J. Fire Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, J. Groark Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, N. L. Fox Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Roth Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Gordon Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline